Keanekaragaman dan Status Konservasi Jenis-Jenis Ikan yang Didaratkan di PPI Batu Belubang Kabupaten Bangka Tengah - Melica, Melica; Pratiwi, Fika Dewi; Gustomi, Andi (Universitas Bangka Belitung, 2024)
Batu Belubang Fish Landing Base (PPI) is one of the PPI in Central Bangka whose fishery business activities are still running today. However, local fishermen still lack information about the protection status and lack of data on the status of these fish species. The lack of data makes fishermen overfisher. Therefore, this study was conducted to identify the species of fish landed at PPI Batu Belubang, classify the fishing gear used by Batu Belubang fishermen and determine the conservation status of the species of fish landed. Data collection will be carried out in March-April 2023 at Batu Belubang PPI. This study used survey and observation methods with qualitative descriptive data analysis. The results showed that there were 12 families identified, namely Carangidae, Clupeidae, Engraulidae, Scombridae, Sphyraenidae, Terapontidae, Ariidae, Leiognathidae, Nemipteridae, Siganidae, Synodontidae and Loligonidae. The classification of fishing gear used by fishermen is lift nets (boat charts and floating charts) and fishing rods. Conservation status based on IUCN found 12 species classified as Least Concern, one species Near Threatened, two species Data Deficient and four species Not Evaluated. Based on the results, it can be concluded that the sustainability of fisheries, especially endangered species, requires management by relevant stakeholders such as socialization from fisheries extension workers regarding conservation status and species of fish that are already endangered.